On waves due to a line source in front of a vertical wall with a gap (Archives of Mechanics - Test, 1998)
In the present paper waves due to presence of a line source in front of a vertical wall with a gap are studied. A simple expression for amplitude of radiated waves at infinity is obtained by application of Green's integral theorem.